2011
DOI: 10.4162/nrp.2011.5.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Anti-doping education and dietary supplementation practice in Korean elite university athletes

Abstract: This study was conducted to investigate relationships and gender differences in dietary supplement (DS) and oriental supplement (OS) prevalence as well as anti-doping awareness during training and the game period. Korea National Sport University athletes (343 male and 136 female) participated in this study and completed DS and OS practice and anti-doping awareness questionnaires. Forty-six percent of athletes used DS during the training period, and there was significantly higher DS use in females (53%) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
(42 reference statements)
2
20
0
Order By: Relevance
“…On the other hand, OS use was 28% with a higher rate for female athletes than male athletes [1]. The current study results showed the same DS and OS prevalence in athletes.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, OS use was 28% with a higher rate for female athletes than male athletes [1]. The current study results showed the same DS and OS prevalence in athletes.…”
Section: Discussionsupporting
confidence: 70%
“…The data showed that, among the supplement users, creatine (37.3%), vitamin (51.8%) and protein (14.8%) users showed signi cant unawareness about the supplements type they consumed (p = 0.05). Furthermore, the current prevalence rate is comparatively similar with past recorded values in developed counties [16,17] and comparatively higher with what has been recorded in some other Asian countries [18,19,20]. Although supplement usage may depend on socio-demographic factors such as gender and age category, the current study was not complied with that.…”
Section: B Attitudes Of Athletessupporting
confidence: 63%
“…Among the dietary supplements protein, vitamin/multivitamin, minerals creatine, electrolyte, and energy drinks/sports drinks have commonly appeared among athletes [19,27,30]. However, despite the maturity in the sports eld, overall athlete population has inclined to the supplements purposely to increase energy/ strength, stay healthy, immune recovery and performance enhancement [17,20,22]. Attitudes, knowledge on doping, and motivation have recognized as the indicators which affect the doping behaviour of athletes [ 8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there can be no guarantee of the purity of any commercial supplement. Supplements use among athletes is widespread [7,16], with by 62.7% of the Japanese national YOG team reporting that they used supplements for health and well-being [17]. It is necessary for coaches to raise athletes' awareness of the possibility that supplements may include substances prohibited under anti-doping regulations.…”
Section: Q Uk_y and Uk_n (N)mentioning
confidence: 99%